Nasal methicillin-resistant Staphylococcus aureus colonization among otherwise healthy children aged between 2 months and 5 years in northern Taiwan, 2005–2010 - Meng-Shan Tsai; Chih-Jung Chen; Tzou-Yien Lin; Yhu-Chering Huang (Journal of Microbiology, Immunology and Infection, 2018)
Background: Community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) infections have been increasingly reported worldwide and are associated with nasal colonization. In Taiwan, available data disclosed a similar trend. We conducted a study for the updated childhood nasal MRSA carriage. Methods: From July 2005 to December 2010, children aged between 2 months and 5 years who presented for a well-child health care visit to a medical center or from kindergarten/daycare center were invited and a nasal swab specimen was obtained for the detection of MRSA. All MRSA isolates were characterized. Results: A total of 3226 children were included and the rate of nasal MRSA carriage was 10.2%. Children aged 2–6 months and >3 years were significantly associated with MRSA carriage, while pneumococcus colonization (p = 0.033) and breastfeeding (p = 0.025) were negatively associated with MRSA carriage. Of the 330 MRSA isolates, a total of 13 pulsotypes with two major patterns (type C, 47.0% and D, 29%) were identified. Most MRSA isolates belonged to two major clones, characterized as sequence type 59 (ST59)/pulsotype C/staphylococcal cassette chromosome (SCCmec) IV/Panton-Valentine leukocidin (PVL)-negative (45.8%) and ST59/pulsotype D/SCCmec VT/PVL-positive (22.7%). Two new clones as ST 508/SCCmec IV (9.7%) and ST573/SCCmec IV (7.3%) emerged and increased markedly since 2007. Conclusion: Between 2005 and 2010, 10.2% of healthy children in northern Taiwan carried MRSA in anterior nares, with the highest carriage rate for infants aged 2–6 months. Two emerging clones, ST 508 and ST 573, were identified and the clinical significance needs further surveillance. Keywords: Methicillin-resistant Staphylococcus aureus, Community-associated, Sequence type 59, Taiwan, Children, Colonization